Identification of chemical constituents of Zanthoxylum heitzii stem bark and their insecticidal activity against the malaria mosquito Anopheles gambiae. Issue 1 (December 2015) - Moussavi, Nastaran; Malterud, Karl; Mikolo, Bertin; Dawes, Dag; Chandre, Fabrice; Corbel, Vincent; Massamba, Daniel; Overgaard, Hans; Wangensteen, Helle
Abstract Background Zanthoxylum heitzii bark extracts have insecticidal properties and have been reported to be used against malaria in Western Africa. Previously, it has been shown that a hexane extract of the bark is toxic to adult females of the mosquitoAnopheles gambiae, a malaria vector. As part of our project on the control of malaria vectors using plant extracts, the phytochemistry ofZ. heitzii bark hexane extract has been investigated with the aim to identify the major components with adulticidal and larvicidal effects onAn. gambiae . Methods Z. heitzii stem bark was extracted with hexane, and the extract was fractionated to isolate major components from the bark, identified by NMR spectroscopy. Isolated compounds were tested for toxicity towards adult femaleAn. gambiae mosquitoes and for larvicidal effects towardsAn. gambiae . Results The alkaloid dihydronitidine, the sesquiterpenoid caryophyllene oxide, the amide pellitorine and the lignan sesamin were identified as the major constituents inZ. heitzii bark. Pellitorine was toxic to both adult insects (LD50 50 ng/mg insect) and larvae (LD50 13 μg/ml). None of the other compounds were toxic to adults, but caryophyllene oxide and sesamin exhibited moderate larvicidal effects (LD50 > 150 μg/ml). A mixture of the four compounds in the same ratio as in the hexane extract showed higher toxicity (LD50 34 ng/mg insect) towards adult insects than the pure compounds. Conclusion The toxicity ofZ. heitzii bark hexane extract toAn. gambiae is mostly due to pellitorine, although interactions between pellitorine and other, inactive constituents may enhance the activity of the extract.